Double beta decay without invoking closure - Pantis, G.; Vergados, J. D. (HNPS Advances in Nuclear Physics, 2020)
The nuclear matrix elements of PU operators entering in the 0v ßß-decay of 76Ge-->76Se have been calculated explicitly in the context of QRPA within the model space 0f7/2 - 0h11/2. T h e validity of the closure approximation has been tested and seems to be quite satisfactory for those matrix elements which are not usually suppressed. Our results indicate that they are dominated by multipoles other than 0+ and 1+ and that the matrix elements are comparable to those of shell model calculations.